PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM - Rachmawati, Ike Devi; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to find out the influence of financial performance to the stock return on miningcompanies which are listed in Indonesia Stock Exchange in 2012-2015 periods. The variables in this research areCurrent Ratio, Debt to Equity Ratio, Earnings Per Share, Return on Asset, and Total Asset Turnover as theindependent variables and stock return as the dependent variable. The population has been obtained by usingpurposive sampling method on mining companies in Indonesia Stock Exchange in 2012-2015 periods and basedon the predetermined criteria 9 mining companies have been selected as samples. So 36 research data have beenobtained. The analysis method has been carried out by using multiple linear regressions and the SPSS(Statistical Product and Service Solutions) 23rd version. The result of the research shows that Debt to EquityRatio, Earning Per Share, Return on Asset , and Total Asset Turnover give positive and significant influence tothe stock return whereas Current Ratio does not give any significant influence to the stock return.Keywords: Debt to equity ratio, earnings per share, return on asset, total asset turn over, stock return.